A Laboratory study of coronal microleakage using four temporary restorative materials - Cruz, E.V (The Journal of the Philippine Dental Association)
Aim: The aim of this study was to com pare the sealing abilities of Fermin and Canseal with the more popular temporary coronal filling materials. Cavit and Caviton.